2008
DOI: 10.1515/jpm.2008.024
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric gel shortens second stage of labor and prevents perineal trauma in nulliparous women: a randomized controlled trial on labor facilitation

Abstract: Objective: To determine whether the obstetric gel shortens the second stage of labor and exerts a protective effect on the perineum. Method: A total of 251 nulliparous women with singleton low-risk pregnancies in vertex position at term were recruited. A total of 228 eligible women were randomly assigned to Group A, without obstetric gel use, or to Group B, obstetric gel use, i.e., intermittent application into the birth canal during vaginal examinations, starting at the early first stage of labor (prior to 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
1
22
1
3
Order By: Relevance
“…Nevertheless, the applied obstetric gels generally reduced the friction force in comparison to distilled water as a reference. The presented procedure thus confirmed the benefit of obstetric gels with respect to childbirth facilitation, which has already been observed in first clinical trials [12].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the applied obstetric gels generally reduced the friction force in comparison to distilled water as a reference. The presented procedure thus confirmed the benefit of obstetric gels with respect to childbirth facilitation, which has already been observed in first clinical trials [12].…”
Section: Discussionsupporting
confidence: 81%
“…Just recently, obstetric gels for labor facilitation in humans have been developed and brought onto the market. In a first randomized controlled study, these obstetric gels significantly shortened the duration of the second stage of labor and significantly reduced the risk for perineal tears in nulliparous women [12].…”
Section: Introductionmentioning
confidence: 99%
“…The HEC gel was used as an intra-vaginal contrast agent for sonographic examination of the cervix during pregnancy (O'Brien et al, 2003). Intermittent application of obstetric gel containing HEC and GLY into the birth canal in a randomised-controlled trial showed a significant reduction in the second stage of labour and a significant increase in perineal integrity (Schaub et al, 2008). No side-effects were observed in this study.…”
Section: Obstetric Applicationsmentioning
confidence: 59%
“…From a point of view of kinetics, friction forces between the child and the vaginal part of the birth canal are opposing the force of myospasms of the womb and can hinder delivery. Inside the birth canal, obstetric gel is a means of reducing friction (Riener et al, 2009;Schaub et al, 2008;Zhuk & Pekhnyo, 2009). It is worthwhile emphasizing that many pharmacologic means of reducing delivery pains and facilitating the course of delivery exist whose application was abandoned in gynecology and obstetrics as a result of complications they can cause, whereas obstetric gel does not contain active pharmaceutical substances.…”
mentioning
confidence: 99%
“…In the present study, the authors examine an obstetric gel containing polyacrylic acid as a bioadhesive agent. A study conducted on use of the gel in Switzerland in 2005 and 2006 on a group of 183 pregnant women reported that its use was closely connected with shortening the second stage of labor and reducing perineal tears (Schaub et al, 2008). Moreover, in the 1950s in Germany and Italy a similar study was performed with the use of a similar substance, hyaluronic acid, in the perineal area in order to reduce abrasions during labor.…”
mentioning
confidence: 99%